Territory, construction and development activity: since «tsunami» to crisis. Explanatory factors and a proposal of indicators at municipal scale in Andalusia - Alfonso Fernández Tabales; Estrella C (Boletín de la Asociación de Geógrafos Españoles)
Resumen